Why Are Newcomers so Happy? Subjective Well-Being of First-Generation Immigrants in Germany - Brockmann, Hilke (Frontiers in Human Dynamics, 2021)
First-generation immigrants are surprisingly satisfied with their life compared to the local population in Germany. Is his because newcomers are particularly resourceful? We test if personality selectivity, purposive adaptation, and social resilience separately or in tandem explain why subjective well-being remains high even in times of objective disadvantage. Using German panel data (GSOEP) from 5,008 first-generation immigrants for the years 1984-2014 and official data, growth curve models show that newcomers are a selected group with respect to their open and less neurotic personalities and that these personal characteristics are distinctly associated with happiness. Also, newcomers immediately compare their income to the standards in the host society but not their family life. This contributes to boosting their subjective well-being as well. For more than 30 years, first-generation immigrants use their country of origin as a reference point thus protecting the positive association of intimate relationships and happiness. Finally, newcomers are highly capable of recovering from social loss. Since the resources used by first-generation migrants to preserve their subjective well-being are unlikely to be confined to Germany, our findings can inform policy making. Most importantly, they suggest that the economic integration of newcomers should be fast and easy while family reunification and integration should follow only with a time lag.